Pengaruh Edukasi Manajemen Chocking terhadap Kemapuan Ibu dalam Menangani Tersedak pada Anak - Ruhaya Asnawi; Rahmat Hidayat Djalil; Faradilla Miftah Suranata (JURNAL RISET RUMPUN ILMU KESEHATAN, 2023)
Choking is an emergency situation that frequently occurs in infants and toddlers and can potentially lead to death if not managed promptly and appropriately. Limited knowledge and skills of parents, particularly mothers, in providing first aid are among the factors that increase the risk of complications resulting from choking incidents in children. This study aimed to determine the effect of choking management education on mothers’ ability to handle choking incidents in children in Pinokalan Subdistrict, Ranowulu District, Bitung City. This study employed a pre-experimental design using a one-group pretest–posttest approach. The study population consisted of 75 respondents, with a sample of 15 mothers who had children aged ≤ 3 years, selected using accidental sampling techniques. The intervention consisted of health education on choking management using standard operating procedure guidelines and structured health education sessions, while mothers’ abilities were assessed using an observation checklist. Data analysis included univariate and bivariate analyses using the McNemar test with a significance level of α = 0.05. The results showed that prior to the educational intervention, most mothers had poor ability in managing choking incidents in children; however, after the intervention, there was a significant improvement in their abilities. The McNemar test yielded a p-value of 0.008, indicating a significant effect of choking management health education on mothers’ ability to manage choking incidents in children. These findings demonstrate that health education plays an important role in improving mothers’ preparedness and skills in dealing with pediatric emergencies. This study is expected to serve as a basis for the development of community-based health education programs as a promotive and preventive effort to reduce morbidity and mortality risks due to choking in children.